Analisis Hadis-Hadis yang Disampaikan Mubaligh di Masjid Agung Baitul Makmur Rejang Lebong - Busra Febriyarni (Jurnal Dakwah dan Komunikasi, 2018)
A Research of living hadis that researcher did this time was in the Great Mosque Baitul Makmur Rejang Lebong. It consideredthat this mosque is a government and largest mosque in Curup City Rejang Lebong.Every shubuh there is always taushiyah there. As comparisons, the researcher also took the Aljihad Mosque and Nurul Huda Curup Mosque. A complete facts of the hadis submitted by the preacher from the 3 mosques. The researcher took 1 month of Ramadan for the research. How are the traditions used by theologians in preaching some hadis, whether they are in accordance with the standard practice of a hadis, that is shahih and hasan or still in dhaif and maudhu category. If qualified shahih and hasan then they should be practiced, but if they qualified dha'if and maudhu so then they must be abandoned. Majority of preachers in these three mosques in particular have delivered some hadis qualified maqbul. Minorities of them still present some hadis that qualified mardud or rejected.